Benefits of Public Expenditures on Sport - Broulíková, Hana Marie, 1989- (2015)
Participation in sport activities brings various benefits to the individuals involved as well as to the society as a whole. One of these benefits is a higher labour productivity following from a lower disease-induced absence rate and from the improved personal work characteristics. This thesis investigates the influence of public money spent in support of sport on labour productivity. The study is based on the data about these expenditures on the level of the Czech municipalities, whereas the expenditures on sport are aggregated over the municipalities belonging to each of the fourteen regions composing the Czech Republic. The performed regression analysis traces the influence of these expenditures on the disease-induced work incapacity rate in the respective region, which constitutes a proxy for labour productivity. The results of the analysis show that municipal expenditures on sport significantly decrease the disease-induced work incapacity: if municipalities in a region spend extra one hundred CZK per person on sport, the disease-induced work incapacity in the following year lowers by 0.064 to 0.083%.